Fleshing out surfaces : Skin in French art and medicine, 1650-1850 - Fend, Mechthild (Book collections on Project MUSE., 2016)
A strong and insightful work which argues that skin is not just any surface an artist can represent, but a highly overdetermined one. Focusing on five French painters - Fragonard, David, Girodet, Benoit and Ingres - it spans the fields of history of art and of medicine.